Strategi Inovatif Penguatan Karakter Anak Berbasis Kearifan Lokal melalui Edukasi Kreatif di Desa Gemaharjo - Seli Septiana Pratiwi; Neni Wahyuningtyas; Annisa Nur Cahyaningrum; Moh. Pebrianto; Syarifah Ambami; Lovita Meisabinawati (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service activity aims to strengthen children's character in Gemaharjo Village, Trenggalek, through creative education based on local wisdom. The main issues include limited resources, lack of teacher training, minimal integration among schools, families, and the community, and inadequate infrastructure for creative activities. The approach involves structured mentoring using experiential learning following Kolb's cycle (concrete experience, reflection, conceptualization, and experimentation). The activities consist of five stages: screening the Tari Turonggo Yakso video, interactive discussion, sack race game, collaborative poster creation, and final reflection. Results show the internalization of core values such as cooperation, discipline, responsibility, and mutual respect, observed through active participation of children aged 7–15. This activity enhances understanding of integrating local wisdom into meaningful, contextual learning models for community involvement.